1975
DOI: 10.1063/1.321434
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric relaxation studies of poly(N-vinylcarbazole) and poly(3-chloro-N-vinylcarbazole) including the effects of sorbed oxygen

Abstract: NMR relaxationtime studies of poly(Nvinyl carbazole) and sorbedO2 effectsThe dielectric relaxation spectrum of poly(N-vinylcarbazole) (PVK) and poly(3-chloro-N-vinylcarbazole) (CLPVK) have been investigated in the temperature range -180-+ 240 DC. Four relaxations are observed in PVK. The a relaxation (225°C) is associated with the glass transition of the polymer. On the basis of oxygen-sorption experiments, the y relaxation (--60°C) has been associated with a rotationallibration of the pendant carbazole group.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
10
0

Year Published

1976
1976
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(11 citation statements)
references
References 15 publications
1
10
0
Order By: Relevance
“…Such mechanism is called as the "wet dog" effect [25]. Akuetey and Hirsh [26] based on an analysis of dielectric measurements for PVK made by Pochan et al [27], have found that the -relaxation in this polymer extrapolated to the mHz frequency range should appear at around 130 K. This frequency range corresponds to an equivalent frequency of thermally stimulated processes, if the heating rate is a few K/min [26]. It means that the detrapping which gives rise to the TL maximum at around 130 K could be induced by the -relaxation in PVK.…”
Section: Thermoluminescencementioning
confidence: 99%
“…Such mechanism is called as the "wet dog" effect [25]. Akuetey and Hirsh [26] based on an analysis of dielectric measurements for PVK made by Pochan et al [27], have found that the -relaxation in this polymer extrapolated to the mHz frequency range should appear at around 130 K. This frequency range corresponds to an equivalent frequency of thermally stimulated processes, if the heating rate is a few K/min [26]. It means that the detrapping which gives rise to the TL maximum at around 130 K could be induced by the -relaxation in PVK.…”
Section: Thermoluminescencementioning
confidence: 99%
“…Thus, the TL maxima often correspond well to the onset of molecular motions, what affords evidence for a significant contribution of the molecular motions to the charge carrier detrapping process [13,44]. It is known, on a basis of dielectric spectroscopy of PVK done by Pochan et al [45], that at around 130 K, the c-relaxation corresponding to the limited rotation of carbazol-9-yl groups appears, if the dielectric experiments are performed in the mHz range. This frequency range corresponds to an equivalent frequency of the thermally stimulated processes (TL, and also TSCthermally stimulated currents or TSD -thermally stimulated depolarisation) if the heating rate is a few K/min.…”
Section: Resultsmentioning
confidence: 96%
“…2b), and amount 390 meV and nearly 100 meV for c-relaxation and d-relaxation, respectively [45]. This is because only an onset of the molecular motions may be sufficient to facilitate the detrapping of the localised charge carriers e.g.…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…The voltage-dependent part of the process more likely corresponds to b-relaxation which occurs at 80 1C and which corresponds to the wagging motion of the carbazole units. 24 The wagging motion of neighbouring carbazoles would significantly change their distance and thus the charge transport between them. Local (nanoscale) heating to 80 1C in the poorly thermally conductive PVK film is plausible since it has been shown that a luminance of 1000 cd m À2 in an OLED can lead to overall temperatures of the active layer of 46 1C.…”
mentioning
confidence: 99%